Pengembangan Media Pembelajaran Interaktif Berbasis Discovery Learning Pada Mata Pelajaran Tata Hidang di Kelas XI SMK Pariwisata Mengwitani - Sri Indah Yani; Made Susi Lissia Andayani; Dessy Seri Wahyuni (Universitas Pendidikan Ganesha, 2022)
This study aims to produce discovery learning-based interactive learning media on tata hidang subjects in class XI of Mengwitani Tourism Vocational School and to find out the responses of teachers and students regarding the design of discovery learning-based interactive learning media on tata hidang subjects in class XI of Mengwitani Tourism Vocational School. This research is a research & development (R&D) type using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results of the calculation of the validity of content experts and media and design experts show that the validity level of 1.00 is included in the